2005
DOI: 10.1207/s15430154jce2002_8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Education for Community Health Aides/Practitioners (CHA/Ps) in Alaska Assessing Comfort with Cancer

Abstract: A total of 402 responses were received from a mailed questionnaire to 477 CHA/Ps. Respondents were predominantly Alaska Native women. Using a 5-point Likert scale from don't know to very comfortable, approximately 50% of CHA/Ps reported feeling "OK" when providing information about cancer risk factors, cancer screening, surviving cancer, and providing care and support. CHA/Ps reported feeling less comfortable with discussing cancer diagnosis, treatment, pain, and loss and grief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Two of these studies foreground the likelihood that AI/AN patients will receive care from non-physician providers, due in part to financial constraints and regional differences in provider availability. One study included a survey of almost 500 community health practitioners in Alaska, who reported that they often felt confident discussing cancer risk factors or care issues, but had less knowledge and comfort around cancer pain 24. The other study, conducted in an urban, nurse-managed primary care center, found that pain-related issues were the most common reason for seeking care 54…”
Section: Resultsmentioning
confidence: 99%
“…Two of these studies foreground the likelihood that AI/AN patients will receive care from non-physician providers, due in part to financial constraints and regional differences in provider availability. One study included a survey of almost 500 community health practitioners in Alaska, who reported that they often felt confident discussing cancer risk factors or care issues, but had less knowledge and comfort around cancer pain 24. The other study, conducted in an urban, nurse-managed primary care center, found that pain-related issues were the most common reason for seeking care 54…”
Section: Resultsmentioning
confidence: 99%
“…In response, the Community Health Aide Program cancer education project team developed and delivered in-person cancer and wellness classes throughout the last decade in Alaska’s CHA/P Basic Training Centers (Anchorage, Nome, Bethel) [7,8]. Unfortunately, Alaska’s geographic challenges (large distances, expensive airfare, and harsh weather patterns) restrict the amount of in-person cancer education that can be made available to CHA/Ps.…”
Section: Introductionmentioning
confidence: 99%
“…And I know how to use the therabands”; quitting tobacco (3), “I've already cut back on my smoking. I'm going to quit!”; and having recommended screening exams (7), “I will get a colon screening – I am 50”.…”
Section: Resultsmentioning
confidence: 99%
“…Although disease prevention and health promotion are part of CHA/P training, only a few hours of the curriculum can be dedicated to these topics, as CHA/Ps’ primary practice is providing direct patient care. To supplement CHAP basic training, two 5-day courses were developed; a CHA/P diabetes course in 1996 (6) and a cancer education course in 1998 (79) which grew out of CHA/Ps’ desire to learn more to better care for the people in their communities.…”
mentioning
confidence: 99%